Digitalization of business processes in adaptation of catering industry to new realities (Covid-19 pandemic) - Mitrofanova, Inna V.; Chernova, Olga A.; Batmanova, Victoria (Serbian Journal of Management, 2022)
The limitation of business and social activity during the crisis caused by the coronavirus in Russia and in the whole world led to the need to adapt the business processes of public catering enterprises to new realities. The goal of research is to study the trends of digital transformations of business processes of public catering enterprises of southern Russia, due to the need to adapt to the factors caused by the pandemic, as well as to assess their “viability” in terms of their use after the end of the coronavirus crisis. To conduct the study, the authors chose content analysis of scientific sources presented in the databases Scopus and Web of Science, which described the cases of development of public catering enterprises during the crisis caused by the coronavirus. As a result of the analysis of Russian and international experience, it was revealed that the set of solutions dealing with digitalization of business processes was focused on the use of technologies that ensure a decrease in perceived health risks, and was expressed both in changing the services provided and in changing the process of their provision. The study identified the following main trends in the digitalization of business processes in the food service industry of Russia. The characteristics of these trends are given from the point of view of their "viability" in the long term. Common problems associated with the use of digital technologies and tools in businesses are identified. The authors came to the conclusion that the digitalization of business processes in Russia will continue after the return to traditional forms of service, since modern consumers tend towards a variety of technological innovations due to their speed and relative ease of use, and the increased availability of mobile technologies that provide search, payment, and other functions also they make it possible to reduce health risks.
Keywords: digital transformations; coronavirus crisis; factors of the Covid-19 pandemic; business processes; food service industry; contactless interactions; adaptation; digital technologies